The Relationship Of Placement And Protection Services To Indonesian Labor In Serang District - Sukhebi Mofea (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The purpose of this study was to determine the service level of the Service Center for the Placement and Protection of Indonesian Migrant Workers in the Serang District. In the Placement and Protection of Indonesian Migrant Workers from Serang Regency. The research method used is a quantitative analysis approach. The data collection technique was through a questionnaire distributing several questions which were distributed to 278 respondents. The results of this study are that service users are dissatisfied with the services provided by the Service Center for the placement and protection of Indonesian workers in the Serang Regency.. Suggestions need for supervision and coordination from the Center for placement and protection of Indonesian workers, related to placement and protection. Socialization is needed which should be held routinely to provide information to workers and should improve the quality of Human Resources and improve other service support facilities